Assessing Trade–Labor Linkages: A Big Step Forward. Issue 1 (2nd January 2019) - Elliott, Kimberly Ann
Abstract : Labor Provisions in Preferential Trade Agreements (LABPTA) are an important and necessary step forward in being able to better assess the role of these trade‐labor linkages in improving workers' lives.